Konflik Perdagangan Minyak Sawit Indonesia dan Malaysia dalam Menghadapi Kebijakan Uni Eropa (EU) - Justa Yijreal Situmorang; Silviani Silviani; Khoirida Rahma; Oot Hotimah (Fakultas Ilmu Sosial dan Hukum, 2023)
The main problem discussed in this research is how the Indonesian and Malaysian Palm Oil Trade Conflict is Facing European Union Policy. Where the conflict that occurred also involved international organizations, namely the European Union (EU), not a conflict between countries. This is certainly interesting considering the good position of Indonesia and the European Union (EU) in the Paris Agreement and the good relations between Indonesia and Malaysia with the European Union (EU), which then gives rise to conflict and has an impact on the environment. The aim of this research is to find out and explain how the conflict between Indonesia and Malaysia with the European Union (EU) occurred and what policies were taken by Indonesia and Malaysia in facing the European Union (EU). Therefore, the researcher took the title, namely the Indonesian and Malaysian Palm Oil Trade Conflict in Facing European Union Policy. With the objectives to be achieved and expected to be able to explain using the research method used, namely method library research. Where this research will use two data collection techniques, namely literature research and sites on the Internet (Websites)